Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru di MTs Yasmida Ambarawa - Hidayat, Dede; Kusuma, Nur Hadi; Umurohmi, Ulfa; Zainuri, Ahmad (Universitas Pahlawan Tuanku Tambusai, 2025)
The leadership of the school principal plays an important role in improving the quality of education in an institution, including in efforts to improve teacher performance. This research method is qualitative. The results of this research are that the leadership of the principal at MTs Yasmida Ambarawa plays a key role in improving teacher performance through motivation, academic supervision, professionalism development, and creating a conducive work environment. The principal's leadership significantly influences the quality of education within an institution, particularly in enhancing teacher performance. This qualitative research explores the principal's role at MTs Yasmida Ambarawa in fostering teacher development through motivation, academic supervision, professional growth, and the establishment of a supportive work environment. The findings indicate that principals motivate teachers by offering emotional support and recognition, conduct academic supervision to ensure effective teaching practices, and facilitate professional development through training and collaborative initiatives.Despite challenges such as administrative burdens and resource constraints, principals employ strategies like task delegation, external partnerships, and persuasive leadership to create a supportive work environment. This research underscores the critical role of strategic leadership in improving teacher performance and, consequently, the quality of education.